(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper has been an attempt to find out the investors awareness and their perception towards Sbi Mutual Funds. A Mutual Fund is a trust that pools the savings of a number of investors who share a common financial goal. The money thus collected is then invested in capital market instruments such as shares, debentures and other securities. The income earned through these investments and the capital appreciation realized is shared by its unit holders in proportion to the number of units owned by them. Thus a Mutual Fund is the most suitable investment for the common man as it offers an opportunity to invest in a diversified, professionally managed basket of securities at a relatively low cost.